Posterior scleritis misdiagnosed as central serous chorioretinopathy: Case report - Lina Jiangbolati; Yan Gao; Qing Peng (Photodiagnosis and Photodynamic Therapy, 2025)
This case report describes a 39-year-old male presenting with serous retinal detachment (SRD) who was initially misdiagnosed with acute central serous chorioretinopathy (CSC). CSC is typically a self-limiting condition, but recurrence occurs in approximately 30–50 % of patients depending on risk factors and disease chronicity. He received antibiotics for suspected infection, but his symptoms persisted without corticosteroid use. After referral to our hospital, posterior scleritis was confirmed through inflammation signs, multimodal imaging (showing optic disc edema, extending SRD, thickened eyewall, and ciliary body detachment), and elevated systemic inflammatory biomarkers. Methylprednisolone therapy relieved symptoms within four days. Follow-up at four months showed complete SRD resolution and choroidal fold regression.This case highlights the diagnostic challenge in patients with SRD, where demographic assumptions—such as the tendency to associate CSC with young males—may delay recognition of inflammatory etiologies like posterior scleritis. Corticosteroids, which may worsen CSC, are essential for treating posterior scleritis—highlighting the critical need for accurate differentiation to avoid therapeutic missteps and irreversible vision loss. Definitive diagnosis necessitates synthesizing ocular examination findings, systemic biomarkers, and multimodal imaging. Clinicians must prioritize integrating clinical, imaging, and laboratory data over relying on isolated SRD or demographic stereotypes to guide management in complex ophthalmic cases.